Narcine atzi Carvalho & Randall, 2003 (Pisces: Narcinidae) - an addition to Indian ichthyofauna - Sujatha, K.; Iswarya Deepti, V. A.; Ravali, V.; Jha, Sneha (Indian Journal of Fisheries, 2016)
A species of electric ray of family Narcinidae, Narcine atzi Carvalho & Randall, 2003 has been recorded for the first time from Indian waters. Five specimens of N. atzi in the length range of 343-415 mm (TL) were collected from demersal shrimp trawl catches at Visakhapatnam, central eastern coast of India. The present paper provides description on morphometric characters of the species along with a comparative account on earlier descriptions.